Data quality requirements for water bills. Issue 6 (10th October 2016) - Moura e Sá, Patrícia; Martins, Rita
Abstract : Purpose: The purpose of this paper is to uncover the customers' concerns with the information disclosed in water services invoices and to analyse them with reference to the data quality dimensions usually proposed in the literature. In the context of services of general interest invoices are particularly relevant as a vehicle to convey information to all consumers. Design/methodology/approach: Based on the principles of quality planning, the research uses a qualitative approach to identify the data quality requirements of water invoices. Customer voices were collected by means of focus groups and their meanings analysed using an affinity diagram. Findings: Findings show that plain language efforts and strategies to enhance trust on the service provided need to be further reinforced. Consumers' requirements together with the regulator recommendations also confirm the data quality dimensions identified in the literature. Practical implications: This research highlights that avoiding technical language and making visible the consequences of different consumption levels on the amounts to be paid is essential when designing water invoices. Moreover, it emphasises that there is still room for improvement in the way the economic regulator performs its role in ensuring the provision of sound information. Originality/value: This research addresses a literature gap by conducting a study on data quality requirements outside the context of information systems for organisations. The study is original because it looks at water invoices as a "product" that can be designed to meet the needs of their users.